2017
DOI: 10.3390/molecules23010023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chemical Variations between Crude and Salt-Processed Anemarrhenae rhizoma Using Ultra-High-Performance Liquid Chromatography–Mass Spectrometry Methods

Abstract: The present study was designed to systematically investigate the chemical profile differences between crude Anemarrhenae rhizoma (CAR) and salt-processed Anemarrhenae rhizoma (SAR). Ultra-high-performance liquid chromatography–quadrupole time-of-flight mass spectrometry (UHPLC–QTOF-MS), coupled with multivariate statistical analysis was used for the discrimination of chemical profiles and the identification of the differentiation of the chemical constitutions of CAR and SAR. In addition, seven main constituent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…The main reason for this difference was the increase in timosaponin BIII content and decrease in timosaponin BII content after AR processing. According to our previous study, timosaponin BII can partially change to timosaponin BIII by C22-O bond cleavage during salt processing of AR [29]. The t max , C max, and AUC values of timosaponin AIII increased markedly (P < 0.05) after oral administration of SAR aqueous extracts compared to those after administration of CAR.…”
Section: Pharmacokinetic Studymentioning
confidence: 73%
See 1 more Smart Citation
“…The main reason for this difference was the increase in timosaponin BIII content and decrease in timosaponin BII content after AR processing. According to our previous study, timosaponin BII can partially change to timosaponin BIII by C22-O bond cleavage during salt processing of AR [29]. The t max , C max, and AUC values of timosaponin AIII increased markedly (P < 0.05) after oral administration of SAR aqueous extracts compared to those after administration of CAR.…”
Section: Pharmacokinetic Studymentioning
confidence: 73%
“…The extraction solutions were concentrated to 100 mL (equivalent to 1.0 g/mL of raw material) to obtain the CAR and SAR aqueous extracts. The five compounds in the extracts were quantitatively determined by a validated HPLC–MS method . The corresponding concentrations of neomangiferin, mangiferin, timosaponin BII, timosaponin BIII, and timosaponin AIII were 3.42, 35.8, 53.5, 12.8, and 12.5 mg/g in the CAR aqueous extract, and 2.80, 33.2, 38.6, 24.2, and 13.4 mg/g in the SAR aqueous extract, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In recent studies, the chemical compositions of SAR were found to markedly different from those of its crude materials. But the differential chemical components before and after processing were explained separately from the type or content 8–10 . Previous studies focused on the changes in chemical composition and efficacy of different processed products of AR.…”
Section: Introductionmentioning
confidence: 99%
“…But the differential chemical components before and after processing were explained separately from the type or content. [8][9][10] Previous studies focused on the changes in chemical composition and efficacy of different processed products of AR. However, it was difficult to find a corresponding relationship between the differential components and effects.…”
Section: Introductionmentioning
confidence: 99%
“…Purification and characterization of these bioactive constituent is thus a quite challenging task . The ESI IM‐MS system is very helpful in this scenario because liquid chromatography (LC) can be directly coupled with this system for separation of complicated herbal medicines and the high sensitivity of MS makes the low concentration component analysis possible . In addition, IM increases the peak capacity, provides structural information and potential isomer separation .…”
Section: Introductionmentioning
confidence: 99%